The relationship between financial compensation and nurse performance in the emergency room of Hermina Jatinegara Hospital - Anugrahwati, Ria; Laela, Sri; Silitonga, Junita (Universitas Aisyah Pringsewu, 2025)
Background: Financial compensation is a significant factor influencing nurse motivation and performance, particularly in the Emergency Department (ED), which has a high workload. Adequate compensation is expected to improve the quality of care and nurse job satisfaction.Objective: To examine the relationship between financial compensation and nurse performance in the Emergency Department of Hermina Jatinegara Hospital.Methods: This study employed a quantitative design with a cross-sectional approach. The population consisted of all emergency room nurses at Hermina Jatinegara Hospital (n = 28), using a total sampling technique. Data were collected using financial compensation (10 items) and nurse performance (12 items) questionnaires, both of which had been tested for validity and reliability. Data analysis was conducted using univariate and bivariate methods with the Chi-square test (? = 0.05).Results: Most respondents were middle-aged (46.4%), female (78.6%), held either a Diploma III (D3) or Bachelor’s (S1) degree in Nursing (50.0% each), and had worked for more than six years (50.0%). The majority of nurses received moderate compensation (53.6%) and demonstrated good performance (53.6%). The Chi-square test results showed a significant relationship between financial compensation and nurse performance (p = 0.000).Conclusion: There is a significant association between financial compensation and nurse performance in the Emergency Department of Hermina Jatinegara Hospital. Implementing fair and proportional compensation policies has the potential to motivate nurses to maintain and enhance their performance quality.